Antibody Responses to Infections with Strains of Plasmodium falciparum Expressing Diverse Forms of Merozoite Surface Protein 2 - Weisman, Simon (American Society for Microbiology, 2001)
Individuals living in areas where Plasmodium falciparum is endemic experience numerous episodes of infection. These episodes may or may not be symptomatic, with the outcome depending on a combination of parasite and host factors, several of which are poorly understood. One factor is believed to be the particular alleles of several parasite proteins to which the host is capable of mounting protective immune responses. We report a study examining antibody responses to MSP2 in 15 semi-immune teenagers and adults living in the Khanh-Hoa area of southern-central Vietnam, where P. falciparum is highly endemic; subjects were serially infected with multiple strains of P. falciparum. The MSP2 alleles infecting these subjects were determined by nucleotide sequencing. A total of 62 MSP2 genes belonging to both dimorphic families were identified, of which 33 contained distinct alleles, with 61% of the alleles being detected once. Clear changes in the repertoire occurred between infections. Most infections contained a mixture of parasites expressing MSP2 alleles from both dimorphic families. Two examples of reinfection with a strain expressing a previously encountered allele were detected. Significant changes in antibody levels to various regions of MSP2 were detected over the course of the experiment. There was no clear relation between the infecting form of MSP2 and the ensuing antibody response. This study highlights the complexity of host-parasite relationship for this important human pathogen.